2019
DOI: 10.1002/solr.201900323
|View full text |Cite
|
Sign up to set email alerts
|

(TiO2(B) Nanosheet)/(Metallic Phase MoS2) Hybrid Nanostructures: An Efficient Catalyst for Photocatalytic Hydrogen Evolution

Abstract: Developing photocatalysts that can efficiently produce hydrogen from water under solar irradiation is highly desired for sustainable and clean hydrogen energy. Herein, it is demonstrated that (TiO 2 (B) nanosheet)/(metallic phase MoS 2 ) hybrid nanostructures have high activity for photocatalytic hydrogen evolution from water. The TiO 2 (B) nanosheets are prepared by solvothermal reaction with TiCl 3 as a precursor in the presence of ethylene glycol. Due to the short transportation distance of charge carriers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…As shown in Figure 4g, the CV area of TM 7–3 remarkably increases upon the introduction of high‐capacitance materials (MoS 2 and Ti 3 C 2 ). [ 42 ] As shown in Figure S10 and Table S1, Supporting Information, a higher average lifetime of TM 7–3 composite (5.76 ns) than that of TiO 2 (4.76 ns) as well by TRPL clearly confirms that TM composite has a longer carrier lifetime. The aforementioned results offer direct evidence that the excellent photocatalytic performance can be significantly triggered by the capacitive properties.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…As shown in Figure 4g, the CV area of TM 7–3 remarkably increases upon the introduction of high‐capacitance materials (MoS 2 and Ti 3 C 2 ). [ 42 ] As shown in Figure S10 and Table S1, Supporting Information, a higher average lifetime of TM 7–3 composite (5.76 ns) than that of TiO 2 (4.76 ns) as well by TRPL clearly confirms that TM composite has a longer carrier lifetime. The aforementioned results offer direct evidence that the excellent photocatalytic performance can be significantly triggered by the capacitive properties.…”
Section: Resultsmentioning
confidence: 77%
“…[ 40 ] To date, molybdenum sulfide (MoS 2 ) with a layered structure, which is reckoned as the cocatalyst candidate most likely to replace precious metals, has sparked intense interests in developing novel MoS 2 ‐based materials for photocatalytic applications. [ 41–44 ] Li and coworkers reported enhancement of the photocatalytic H 2 production activity of CdS by loading MoS 2 as cocatalyst. [ 45 ] Yuan et al reported the 2D–2D heterojunction between MoS 2 nanosheets and (001) TiO 2 nanosheets serve as decisive factor in improving the photocatalytic H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Among them, transition metal sulfides have received extensive attention from researchers because of their unique electronic structure, tunable optical properties, suitable band gap, and band edges. [7][8][9] Transition metal sulfides such as MoS 2 , CdS, ZnIn 2 S 4 , and WS 2 have shown good effect in photocatalytic H 2 evolution, O 2 evolution, and pollutant degradation. [10][11][12][13] Notably, ZnS has good thermal stability, high electron mobility, nontoxic, water-insoluble, and relatively cheap cost, which was considered to be a more ideal catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It has become a research focus in energy and the environment. , The photocatalytic efficiency depends on the light absorption intensity and carrier transfer efficiency of photocatalysts. To date, excellent materials such as graphene, molybdenum disulfide, and titanium dioxide (TiO 2 ) have been developed for the photocatalytic processes. …”
Section: Introductionmentioning
confidence: 99%